ALLIED MILITARY CURRENCY OF THE SECOND WORLD WAR; A STUDY IN EMERGENCY PAPER MONEY - Van der Waag, Ian (Scientia Militaria - South African Journal of Military Studies, 2012)
Paper money originated in times when gold and silver coinage were in short supply and therefore, in a sense, all paper money is a substitute for specie. However, there have been circumstances when even the supply of paper money was inadequate. On such occasions various forms of emergency money have made their appearance.